Analysis Of The Influence Of Dividend Policy On Company Value In Banking Sector Companies In 2019-2022 - Tysa Blyna Barus; Wan Fachruddin (International Journal of Management, Economic and Accounting, 2025)
This research aims to see the influence that dividend policy has on company value in companies operating in the banking sector in the period 2019 to 2022. This research uses descriptive research with the data collection technique used is documentation study. The data analysis technique used is simple linear regression. The results of this research show that there is a significant influence on dividend policy on company value in banking sector companies in the period 2019 to 2022 with an influence size of 30.7%, while 69.3% is influenced by other factors.